Fasilitasi Masyarakat Dusun Kerep Desa Wagirkidul dalam Pengolahan Limbah Kayu sebagai Kerajinan yang Bernilai Ekonomi - Prasetyo, Eko Nur; Fitriawan, Fuad; Ulfa, Risa Alfiyah (Social Science Academic, 2023)
Facilitating community empowerment is an important strategy in building a sustainable and inclusive village economy, where village communities can obtain greater economic benefits and improve their quality of life. This training aims to help village communities develop their regional economic potential to increase people's income and welfare. The method used in this community service is Utilization of Wood Waste as a handicraft product that has economic value in training and mentoring and facilitation. The result of this dedication is that facilitating community empowerment can be an effective strategy to improve the village economy. Facilitation can be obtained by applying various relevant theories, such as community empowerment, local economic development, social entrepreneurship, sustainable skills production and facilitating the necessary activities. In practice, community empowerment facilitation and training must be carried out in a participatory manner by involving village communities, especially village youth, in planning and developing businesses that benefit them.